Local cortical thickness predicts somatosensory gamma oscillations and sensory gating: A multimodal approach - Amy L. Proskovec (NeuroImage, 2020)
Two largely distinct bodies of research have demonstrated age-related alterations and disease-specific aberrations in both local gamma oscillations and patterns of cortical thickness. However, seldom has the relationship between gamma activity and cortical thickness been investigated. Herein, we combine the spatiotemporal precision of magnetoencephalography (MEG) with high-resolution magnetic resonance imaging and surface-based morphometry to characterize the relationships between somatosensory gamma oscillations and the thickness of the cortical tissue generating the oscillations in 94 healthy adults (age range: 22–72). Specifically, a series of regressions were computed to assess the relationships between thickness of the primary somatosensory cortex (S1), S1 gamma response power, peak gamma frequency, and somatosensory gating of identical stimuli. Our results indicated that increased S1 thickness significantly predicted greater S1 gamma response power, reduced peak gamma frequency, and improved somatosensory gating. Furthermore, peak gamma frequency significantly and partially mediated the relationship between S1 thickness and the magnitude of the S1 gamma response. Finally, advancing age significantly predicted reduced S1 thickness and decreased gating of redundant somatosensory stimuli. Notably, this is the first study to directly link somatosensory gamma oscillations to local cortical thickness. Our results demonstrate a multi-faceted relationship between structure and function, and have important implications for understanding age- and disease-related deficits in basic sensory processing and higher-order inhibitory function.